Impact of COVID-19 on individual mental health and maternal health services in Ethiopia: systematic review and meta-analysis - Alie, Melsew Setegn; Girma, Desalegn; Negesse, Yilkal; Adugna, Amanuel; Abebe, Gossa Fetene (Frontiers in Public Health, 2024)
The COVID-19 pandemic has caused a major outbreak in the 21st century and has led to significant mental health hazards worldwide. To address this issue, a systematic review has been conducted to analyze existing literature on the impact of COVID-19 on the psychological well-being of the general population, as well as the associated risk factors.A comprehensive search was carried out on PubMed, Embase, Medline, Web of Science, and Scopus databases, covering all available literature up until February 20, 2024. This search was conducted in accordance with the PRISMA guidelines, ensuring a systematic approach. The selection of articles was based on predetermined eligibility criteria, ensuring the inclusion of appropriate and suitable research. In the final analysis, a total of 15 articles focusing on depression and anxiety, 11 articles on stress, and 7 articles on psychological problems were included.These articles specifically examined the outcome variables within the context of English language and specific areas. For the meta-analysis on maternal health services, 11 articles were included for family planning, 25 articles for postnatal care services, 16 articles for institutional delivery, and 14 articles for safe abortion services. These articles were carefully selected for the final pooled analysis.Result: According to a recent systematic review, anxiety, depression, stress, and psychological distress have been prevalent in Ethiopia during the COVID-19 pandemic, with rates of 40%, 41%, 23%, and 41%, respectively. The review also identified various sociodemographic factors that have impacted the country's response to the pandemic, including female gender, age, marital status, incarceration, low income, and lack of social support. Furthermore, the review found that maternal health services have experienced significant reductions during the pandemic.The COVID-19 pandemic has led to a significant increase in psychological distress, which in some cases, is severe enough to require clinical treatment. It is crucial to prioritize efforts to address the negative impact of COVID-19 on mental health as a global public health priority. Additionally, it is important to pay attention to maternal health services during COVID-19 mitigation programs.